Human Corruption as The Effect of Modern Technology as Represented in Okky Madasari's "The Last Crowd" - Johariani, Hana Septiana; Hetami, Fatma (Rainbow : Journal of Literature, Linguistics and Culture Studies, 2019)
Modern technology plays big roles in influencing human life, especially millenial generation. However , it can create human corruption due to its function abuse. The objectives of this study are: 1) to explain how human corruption is described in Okky Madasari’s The Last Crowd and 2) to explain how the modern technology creates human corruption as described in Okky Madasari’s The Last Crowd. The methodology used in this study was descriptive-qualitative. This study analyzed the novel using Levi Strauss’ theory. There were two objects of the study, namely material object which was The Last Crowd novel and formal object from the analysis of the novel using Levi Strauss’ theory. The results of the study are as follows: 1) Human Corruption was described in Okky Madasari’s The Last Crowd through how the characters in the novel use modern technology unwise until it has a bad effect. Human corruption is divided into three kinds of corruption; corruption in time, corruption in function and corruption in behavior. 2) Human Corruption is created due to the influence of technology towards Jayanegara, which triggers him to be trapped in it. It shows when he decides to make a pseudo-identity for being a winner and a revenger. Keywords: Human Corruption, Modern Technology, Structuralism